Intermediate transverse stiffener requirements of high-strength steel plate girders considering postbuckling capacity - Xiao, Yong; Xue, Xuan Yi; Sun, Fei Fei; Li, Guo Qiang (Engineering structures, 2019)
•Requirement of intermediate transverse stiffeners in HSS plate girders was investigated.•AASHTO design equations can not be directly used for transverse stiffeners in HSS plate girders.•Additional out-of-plane deflection leads to an adverse effect on shear resistance. The postbuckling capacity of HSS plate girders is larger than that of mild steel plate girders because of the differences in material properties. Hence, to fully develop the postbuckling capacity, the intermediate transverse stiffener requirement of HSS plate girders could be different from that of mild steel plate girders. The plate girders concerned in this study are without a longitudinal stiffener. To investigate the aforementioned issue, the minimum moment of inertia requirements of intermediate transverse stiffeners in HSS and mild steel plate girders are studied through the finite element analysis (FEA). After the comparison between the FEA results and the results from the design equations in AASHTO LRFD, it states that the design equations in AASHTO LRFD could not be directly used in the design of intermediate transverse stiffeners in HSS plate girders. Hence, based on the FEA results, a new equation is proposed to predict the minimum moment of inertia requirement of intermediate transverse stiffeners in HSS plate girders. Furthermore, because of the difference in the resistant capacity between HSS and mild steel plate girders, the maximum additional out-of-plane deflection of the intermediate transverse stiffener in HSS plate girders corresponding to the ultimate shear resistance is significantly larger than that of the intermediate transverse stiffener in mild steel plate girders. Hence, there is a noteworthy adverse effect caused by the additional out-of-plane deflection of the intermediate transverse stiffener on the shear resistance of HSS plate girders with the maximum limit value set.